Winners vs. losers: Schistosoma mansoni intestinal and liver eggs exhibit striking differences in gene expression and immunogenicity - Peterková, Kristýna; Konečný, Lukáš; Macháček, Tomáš; Jedličková, Lucie; Winkelmann, Franziska; Sombetzki, Martina; Dvořák, Jan (PLoS pathogens, 2024)
The eggs of the blood fluke Schistosoma mansoni are the main cause of the clinical manifestations of chronic schistosomiasis. After laying, the egg "winners" attach to the endothelium of the mesenteric vein and, after a period of development, induce the growth of a small granuloma, which facilitates their passage to the intestinal lumen. Egg "losers" carried by the bloodstream to non-specific tissues also undergo full development and induce large granuloma formation, but their life ends there. Although these trapped eggs represent a dead end in the parasite life cycle, the vast majority of studies attempting to describe the biology of the S. mansoni eggs have studied these liver-trapped "losers" instead of migrating intestinal "winners". This raises the fundamental question of how these eggs differ. With robust comparative transcriptomic analysis performed on S. mansoni eggs isolated 7 weeks post infection, we show that gene expression is critically dependent on tissue localization, both in the early and late stages of development. While mitochondrial genes and venom allergen-like proteins are significantly upregulated in mature intestinal eggs, well-described egg immunomodulators IPSE/alpha-1 and omega-1, together with micro-exon genes, are predominantly expressed in liver eggs. In addition, several proteases and protease inhibitors previously implicated in egg-host interactions display clear tissue-specific gene expression patterns. These major differences in gene expression could be then reflected in the observed different ability of liver and intestinal soluble egg antigens to elicit host immune responses and in the shorter viability of miracidia hatched from liver eggs. Our comparative analysis provides a new perspective on the biology of parasite's eggs in the context of their development and tissue localization. These findings could contribute to a broader and more accurate understanding of parasite eggs interactions with the host, which have historically been often restricted to liver eggs and sometimes inaccurately generalized.
Keywords: proteiny červů; střeva; Ovum; ovum; Schistosomiasis mansoni; vaječné proteiny; antigeny helmintové; Helminth Proteins; Animals; schistosomiasis mansoni; játra; ženské pohlaví; zvířata; myši; Antigens, Helminth; Liver; Intestines; Mice; Female; Egg Proteins; Schistosoma mansoni